1994
DOI: 10.1111/j.1438-8677.1994.tb00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Transport of Inorganic Phosphate and C3‐ and C6‐Sugar‐Phosphates across the Envelope Membranes of Tomato (Lycopersicon esculentum) Leaf‐Chloroplasts, Tomato Fruit‐Chloroplasts and Fruit‐Chromoplasts

Abstract: Plastidial envelope membranes were isolated from tomato (Lycopersicon esculentum) leaves and green and red tomato fruits by isopycnic discontinuous sucrose density gradient centrifugation. Solubilized envelope membrane proteins were reconstituted into liposomes. Transport measurements revealed that the phosphate translocator from tomato leaves transports inorganic phosphate, 3-phosphoglycerate and triosephosphates. The phosphate translocators of green and red fruit plastids catalyze, in addition to the transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
0
25
1
Order By: Relevance
“…A general hexose phosphate translocator that transports Glc6P and, in addition, Glc1P has been demonstrated to exist in tomato fruits (Schünemann and Borchert, 1994) and wheat endosperm (Tetlow et al, 1996), or the presence of such an activity has been deduced indirectly from the observation of Glc1P-dependent starch synthesis, for example, in wheat endosperm (Tyson and ap Rees, 1988), maize Glucose 6-Phosphate Transporter 113 endosperm (Neuhaus et al, 1993), and potato tubers (Naeem et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A general hexose phosphate translocator that transports Glc6P and, in addition, Glc1P has been demonstrated to exist in tomato fruits (Schünemann and Borchert, 1994) and wheat endosperm (Tetlow et al, 1996), or the presence of such an activity has been deduced indirectly from the observation of Glc1P-dependent starch synthesis, for example, in wheat endosperm (Tyson and ap Rees, 1988), maize Glucose 6-Phosphate Transporter 113 endosperm (Neuhaus et al, 1993), and potato tubers (Naeem et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Because these plastids are normally not able to generate hexose phosphates from C3 compounds due to the absence of fructose 1,6-bisphosphatase activity (Entwistle and ap Rees, 1988), they rely on the import of cytosolically generated hexose phosphates as the source of carbon for starch biosynthesis and, in addition, for the oxidative pentose phosphate pathway. The results of transport measurements with intact organelles or reconstituted tissues from different plants suggest that this transport is mediated by a phosphate translocator that imports hexose phosphates in exchange with inorganic phosphate or C3 sugar phosphates (Borchert et al, 1989(Borchert et al, , 1993 Hill and Smith, 1991, 1995; Neuhaus et al, 1993; Flügge and Weber, 1994;Schünemann and Borchert, 1994;Flügge, 1995;Schott et al, 1995;Quick and Neuhaus, 1996).In nongreen tissues from most plants studied to date, glucose 6-phosphate (Glc6P) is the preferred hexose phosphate taken up by nongreen plastids. However, in amyloplasts from wheat endosperm, glucose 1-phosphate (Glc1P) rather than Glc6P is the precursor of starch biosynthesis (Tyson and ap Rees, 1988;Tetlow et al, 1994).…”
mentioning
confidence: 99%
“…Interestingly, a similar situation has been demonstrated for other closely related types of plastid. Schu$ nemann and Borchet [26] showed that tomato fruit chloroplasts and chromoplasts are able to transport Glc1P in counter exchange with P i . In contrast, chloroplasts and chromoplasts purified from sweet pepper fruits (both species belong to the Solanaceae) were not able to import Glc1P ia a hexose phosphate transporter ( [13] ; H. E. Neuhaus, B. Camara, W. P. Quick, and T. Mo$ hlmann, unpublished work).…”
Section: Transport Of Glc6p P I and Other Phosphorylated Intermediatmentioning
confidence: 99%
“…The stimulatory effect of PEP on P i import has already been demonstrated for isolated pea root and embryo plastids [29,30], and for envelope membranes from tomato fruits [26]. It still remains unclear whether there is a specific metabolic requirement for PEP\P i exchange in heterotrophic plastids (e.g.…”
Section: Transport Of Glc6p P I and Other Phosphorylated Intermediatmentioning
confidence: 99%
“…Acyl CoA thioesterase (ACT) was measured according to Schtinemann and Borchert (1994) Determination of phosphatidylcholine (PC) protein and Chl. The analysis of PC has been described previously (Matile and Schellenberg 1996).…”
mentioning
confidence: 99%